Dalbergiella welwitschia (Baker) Baker f. alkaloid-rich extracts attenuate liver damage in streptozotocin-induced diabetic rats - Ajiboye, Basiru Olaitan; Dada, S; Fatoba, H.O.; Lawal, O.E.; Oyeniran, O.H.; Adetuyi, O.Y.; Olatunde, A.; Bakhtiar, M. Taher; Khotib, Junaidi; Darnis, Deny Susanti; Oyinloye, Babatunji Emmanuel (Elsevier, 2023)
This experiment was conducted to evaluate the Dalbergiella welwitschia alkaloid-rich extracts on liver damage in streptozotocin-induced diabetic rats. Hence, to induce diabetes, 45 mg/kg body weight of streptozotocin was intraperitoneally injected into the Wistar rats. Subsequently, 5 % (w/v) of glucose water was given to the induced animals for 24 h. Thus, the animals (48) were grouped into five groups (n = 8), containing normal control (NC), diabetic control (DC), diabetic rats placed on low (50 mg/kg body weight) and high (100 mg/kg body weight) doses of D. welwitschi alkaloid-rich leaf extracts (i.e. DWL and DWH respectively), and diabetic rats administered 200 mg/kg body weight of metformin (MET). The animals were sacrificed on the 21st day of the experiment, blood and liver were harvested, and different liver damage biomarkers were evaluated. The results obtained demonstrated that diabetic rats administered DWL, DWH and MET significantly (p < 0.05) increased hepatic AST, ALT, albumin, SOD, CAT, GSH, and GPX levels when compared to DC with no significant (p > 0.05) different when compared with NC. Also, diabetic rats administered DWL, DWH and MET revealed a significant (p < 0.05) decrease in GGT and MDA levels, as well as, fragmented DNA and protein carbonyl levels when compared to DC with no significant (p > 0.05) different when compared with NC. In addition, histological ex- amination revealed that diabetic rats placed on DWL, DWH and MET normalized the hepatocytes. Consequently, it can be inferred that alkaloid-rich extracts from D. welwitschi leaf could be helpful in improving liver damage associated with diabetes mellitus rats.